What does critical health education in schools look like? Two ethnographic narratives of critical practice. (October 2019) - Fitzpatrick, Katie; Allen, Jean M
Background: Many health education scholars over the last 20 years have argued that critical approaches to the discipline are needed. Despite these calls, there are few published examples of actual critical practice in action in school classrooms. Some have argued that part of the explanation for this lacuna lies in a dichotomy in the field between 'traditional' approaches to health education and more critical approaches. Purpose and Methods: This article draws on an ethnographic study of schools in Aotearoa New Zealand and shares two different narratives of what we identify as critical approaches to health education. New Zealand is unique in that health education is a credentialed subject in senior high school that allows access to national qualifications. We outline the approaches of two different teachers within this system, and evaluate these alongside key literature in the field, and five pedagogical themes. Conclusions: Teachers who engage with critical classroom practice are also likely to include traditional and biomedical teaching approaches. Rather than viewing this as problematic, we argue that health education programmes that value criticality will also value traditional forms of health knowledge, while simultaneously questioning them. Such an approach is necessarily messy but is more successful when teachers embrace a pedagogy of uncertainty.